Controlling Childhood Myopia Progression: A Systematic Review of Interventions - Sadeghi, Alireza; Moravej, Raheleh; Valipour , Anahita; Khabazkhob , Mehdi (Journal of Ophthalmic and Optometric Sciences, 2025)
Purpose: To synthesize evidence on risk factors and interventions for slowing myopia progression in children and adolescents. Methods: PubMed, Scopus, Embase, and Web of Science were searched through December 2023. Eligible studies included randomized and observational designs evaluating environmental factors, specialized spectacle lenses (defocus incorporated multiple segments [DIMS], highly aspherical lens [HAL], slightly aspherical lens [SAL]), multifocal or dual-focus soft contact lenses, orthokeratology, low-dose atropine, and repeated low-level red-light therapy. Two reviewers independently screened and extracted data. Risk of bias was assessed with Cochrane RoB 2 for randomized trials and the Newcastle–Ottawa Scale for observational studies. Outcomes were annual change in spherical equivalent refraction (diopters/year) and axial length (millimeters/year). Results: Increased outdoor time was consistently associated with reduced incidence and slower progression. Specialized spectacle lenses (DIMS, HAL, SAL) and dual-focus/multifocal soft contact lenses slowed refractive change and axial elongation compared with single-vision controls. Orthokeratology effectively reduced axial elongation in appropriately selected eyes. Low-dose atropine produced dose-dependent benefits, with 0.05% generally more effective than 0.01%; rebound varied with dose, treatment duration, and tapering. Emerging evidence for red-light therapy suggested short-term efficacy, but long-term safety and rebound remain uncertain. Combination strategies, such as atropine plus optical interventions, showed additive effects, though data are limited. Conclusions: Outdoor exposure, low-dose atropine (≈0.05%), DIMS/HAL/SAL spectacle lenses, multifocal or dual-focus soft contact lenses, and orthokeratology show the strongest evidence for slowing childhood myopia. Combination therapy may enhance outcomes, while red-light therapy remains promising but investigational, with long-term safety and rebound still uncertain.